Targeted-based Nanocarriers for Control of Non-Hodgkin Lymphoma: Current Aspects and Future Perspectives - Hiware, Monika S. (Asian Journal of Pharmaceutics (AJP), 2024)
Oncology faces many challenges with non-Hodgkin lymphoma (NHL) a varied group of lymphatic system tumors. Immunotherapeutic methods have supplemented or replaced chemotherapy for NHL treatment. Immune checkpoint inhibitors improve NHL patient outcomes and quality of life. CAR-T cell treatments also enhance patient prospects. Monoclonal antibody therapy is advancement. Several treatments are still used. Radiation therapy is a part of this. Multimodal therapy approaches also include stem cell transplantation. The study also examines treatment resistance and long-term side effects. Nano medicine uses nanomaterial’s to treat cancer. Oncology entered a new age. This study gives hope for nanomaterial-based NHL treatment. A treatment more successful, focused and humane.